Therapies for spinal cord injury: perspective from industry - Blight, Andrew (Henry Stewart Talks, 2011)
The problems associated with developing therapies for acute spinal cord injury, Need for reliable animal models, Too many approaches appear to work, Difficulties inherent in the clinical trial process, The importance of establishing a clinically meaningful effect, Defining useful primary endpoints